2017
DOI: 10.1242/jcs.195412
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of E3 ligases involved in lysosomal sorting of the HIV-1 restriction factor BST2

Abstract: The cellular protein BST2 (also known as tetherin) acts as a major intrinsic antiviral protein that prevents the release of enveloped viruses by trapping nascent viral particles at the surface of infected cells. Viruses have evolved specific strategies to displace BST2 from viral budding sites in order to promote virus egress. In HIV-1, the accessory protein Vpu counters BST2 antiviral activity and promotes sorting of BST2 for lysosomal degradation. Vpu increases polyubiquitylation of BST2, a post-translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…Since NS1 does not possess ubiquitin function, it must do so by taking help from ubiquitins involved in TGF-β signaling. A handful of ubiquitins such as Smurf2 and CHIP/Stub1 are known to interact with Smad family proteins [15,[33][34][35]. Our results con rmed that these E3 ligases have different preferences during DENV replication and NS1 expression.…”
Section: Discussionsupporting
confidence: 64%
“…Since NS1 does not possess ubiquitin function, it must do so by taking help from ubiquitins involved in TGF-β signaling. A handful of ubiquitins such as Smurf2 and CHIP/Stub1 are known to interact with Smad family proteins [15,[33][34][35]. Our results con rmed that these E3 ligases have different preferences during DENV replication and NS1 expression.…”
Section: Discussionsupporting
confidence: 64%
“…This finally results in the downregulation of surface levels of BST-2, thereby allowing normal rates of virion release in the presence of Vpu [ 77 , 85 , 137 , 138 ]. BST-2 is constitutively regulated by ubiquitination and lysosomal degradation mediated by the cellular E3 ubiquitin ligases March8 and NEDD4 (Neural precursor cell Expressed Developmentally Down-regulated protein 4) [ 139 ]. It is still a matter of debate however, whether Vpu also uses the endo-lysosomal system for BST-2 counteraction.…”
Section: Counteraction Of Restriction Factors By Viral Auxiliary Pmentioning
confidence: 99%
“…Next we found that these E3 ligases utilize the lysosomal pathway. Utilization of both protetosomal and lysosomal mediated pathway by E3 ligases in enveloped/RNA virus infection is well reported 19,30 . Utilization of such selective pathways during infection may be the one of the biological signatures of DENV pathogenesis.…”
Section: Dengue Virus Ns1 Blocks the Nuclear Translocation Of Smad3mentioning
confidence: 99%